M2 macrophage-derived extracellular vesicles (EVs) miR-155-5p promotes pulmonary fibrosis via epithelial-mesenchymal transition in lung epithelial cells - Shuhong Guan; Ying Ding; Tianyu Chen; Junkang Huangfu; Long Zhang; Xiyao Chen; Jun Zhou (Molecular Biology Reports, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Lower crustal modification at the margin of the North China Craton: Multi-proxy geochemical and isotopic imaging constraints from the Late Mesozoic granitoids in Jiaodong Peninsula - Can-Can Wang; Li-Qiang Yang; Xue Gao; Wen-Yan He; Lei Ju; Dong Xie; Long Wang; Shi-Yao Zhai; Wei Yang; Nan Li; Zheng-Jiang Ding; Jun Deng (Journal of Asian Earth Sciences, 2026)

Operationalizing the serviceshed concept to enhance the effectiveness and equity of flood regulation services in systematic conservation planning - Xue Ding; Jun-Long Huang; Yu Tao; Jiman Li; Henghui Xi; Weixin Ou (Environmental Impact Assessment Review, 2026)

Wheat germ protein in functional foods: structure, processing, applications, and mechanistic insights - Long Pan; Jing-Yang Cai; Ai-Mei Liao; Lin-Lin Ding; Yin-Chen Hou; Ji-Hong Huang; Xin Wang; Ya-Wei Zhao; Na Liu; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

From metabolic reprogramming to diagnostic tool: A machine learning framework identifies biomarkers for soil microplastic stress in rice - Ding Sheng; Yao Liu; Shanshan Yin; Yaowu Cao; Long Teng; Kejie Cai; Hongbing Chen; Jun Cao; Zongqing Ding; Zukai Zhang; Jiong Gao; Chen Yang; et al. (Journal of Hazardous Materials, 2026)

Composition characteristics of the distillation waste residue from coal gasification crude phenol and pyrolysis product distribution of the corresponding residue - Jing Zhou; Bao-Kun Shi; Qing-He Ma; Ya-Ya Ma; Jie Yuan; Wen-Long Mo; Feng-Jun Ding; Bing Hu; Xing Fan; Xian-Yong Wei; Hai-Bao Huang (Fuel, 2026)

A comparison of in-situ and ex-situ phosphonate HEDP removal from industrial reverse osmosis concentrate by Fe(II)/calcium peroxide process: Implications for total phosphorus (TP) management - Jin Xia; Yi Wang; Xiaochang Huang; Xiang Li; Xuejun Long; Jun Wan; Jiaqi Ding; Fei Pan (Journal of Environmental Chemical Engineering, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Phytoplankton and carbon biomass dynamics in the South China Sea: responses to shelf-oceanic gradients and tropical cyclone - Changling Ding; Xingzhou Wang; Yi Long; Zishi Liu; Jun Sun (Marine Life Science & Technology, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Purification and regeneration of spent graphite via a short-process combining microwave irradiation and acid leaching - Tingyu Chen; Ziwen Ying; Long Ding; Jun Liu; Zhen Shang; Shengming Xu; Yinghe Zhang (Chemical Engineering Journal, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Long-term alkaline deactivation of Cu-based catalyst in formaldehyde ethynylation: Mechanism and kinetic analysis - Hui-Long Wei; Zuo-Qian Jihou; Xiao-Qi Liu; Ya-Jun Qiu; Tao Ding; Feng Song; Xue-Gang Ji; Peng-Fei Zhang; Zheng-Hong Luo (Chemical Engineering Journal, 2025)

In vitro inhalation bioaccessibility for PM10-bound neonicotinoids: method development, effects of hydrophobicity, and its implication in health risk assessment - Hui Liu; Mei-Yang Zheng; Cheng Ye; Rengzong Shu; Xi-Long Zhang; Qi Di; Jin-Jian Ding; Wen-Jun Hong (Environmental Geochemistry and Health, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Process Parameters of HSCM Pile Formation in Marine Soft Soils - Jun-nan Zhao; Zhong-ling Zong; Hang Cen; Pai Jiang; Wen-long Ding; Hong-zhang Huang (Geotechnical and Geological Engineering, 2025)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Unveiling potential roles of earthworms in mitigating the presence of virulence factor genes in terrestrial ecosystems - Shu-Ting Xie; Dong Zhu; Ya-Qiong Song; Yong-Guan Zhu; Long-Jun Ding (Journal of Hazardous Materials, 2024)

Effects of three different protein levels on the growth, gonad development, and physiological biochemistry of female Pengze crucian carp (Carassius auratus var. Pengze) broodstock - Jun Xiao; Fan Long; Liyun Ding; Yuan Yao; Weihua Wu; Yilong Fu; Wenjing Chen (Frontiers in Marine Science, 2024)
A 56-days feeding experiment was conducted to evaluate the effect of dietary protein levels on fish growth, gonad development, and physiological biochemistry of female Pengze crucian carp ( Carassius auratus var. Pengze) broodstock. Three isoenergetic diets were formulated, and the crude protein levels were 26.85%, 35.73% and 44.38%, the lipid levels were 7.39%, 7.92% and 7.91%, respectively. The results showed that the weight gain rate (WGR), the specific growth rate (SGR) and the protein efficiency ratio (PER) of the female Pengze crucian carp broodstock increased significantly and the feed conversion ratio (FCR) decreased significantly when the dietary protein level was 35.73% ( P < 0.05). The WGR, the SGR and the PER were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). Increasing dietary protein levels led to a significant increase in the gonad index and the egg menstrual length of the female Pengze crucian carp broodstock ( P <0.05). The higher protein levels resulted in a significant increase in total amino acids, total essential amino acids, and total nonessential amino acids ( P <0.05). The varying ovaries of each group of total saturated fatty acids, total highly unsaturated fatty acids, and total polyunsaturated fatty acids all increased significantly with increasing protein levels ( P <0.05). Furthermore, the aspartate transaminase (AST), low-density lipoprotein cholesterol (LDLC), and malondialdehyde (MDA) contents in plasma were significantly lower in the 35.73% and 44.38% groups than in the 26.85% group ( P < 0.05). The 35.73% group exhibited the highest plasma superoxide dismutase (SOD) activity,. The plasma vitellogenin (VTG), estradiol 2 (E2), and progesterone (PROG) in plasma of female Pengze crucian carp broodstock were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). The results showed that the addition of an appropriate amount of protein to the feed can significantly improve the growth, gonadal development, and health of female Pengze crucian carp. In this study, the effect of 35.73% protein concentration was better than in the other two groups.

Seasonal variations of profiles of antibiotic resistance genes and virulence factor genes in household dust from Beijing, China revealed by the metagenomics - Zhi-Zi Zhou; Jasmine Zhu; Yue Yin; Long-Jun Ding (Science of The Total Environment, 2024)

Low-voltage stimulated denitrification performance of high-salinity wastewater using halotolerant microorganisms - Long Chen; Hai Xiang; Li-Ting Zhou; Yan-Qing Zhang; Yang-Cheng Ding; Di Wu; Nan-Wen Zhu; Yi-Feng Zhang; Hua-Jun Feng (Bioresource Technology, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Exploring ecological effects of arsenic and cadmium combined exposure on cropland soil: from multilevel organisms to soil functioning by multi-omics coupled with high-throughput quantitative PCR - Xin-Yue Ren; Yu-Ling Zheng; Zhe-Lun Liu; Gui-Lan Duan; Dong Zhu; Long-Jun Ding (Journal of Hazardous Materials, 2024)

Selective enrichment of virulence factor genes in the plastisphere under antibiotic and heavy metal pressures - Lu Wang; Tian-Lun Zhang; Qian Xiang; Chen-Xi Fu; Min Qiao; Long-Jun Ding; Dong Zhu (Journal of Hazardous Materials, 2024)

Oral-based nanoparticle-wrapped dsRNA delivery system: a promising approach for controlling an urban pest, Blattella germanica - Gui-Jun Long; Xuan-Zheng Liu; Huan Guo; Meng-Qi Zhang; Lang-Lang Gong; Yun-Feng Ma; Youssef Dewer; Wu-Jia Mo; Ling-Wen Ding; Qin Wang; Ming He; Peng He (Journal of Pest Science, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Confining pressure forecasting of shield tunnel lining during construction based on LSTM-PSO models combined with the multi-output recursive strategy - Xiao-Wei Ye; Yu-Jun Wei; Xiao-Long Zhang; Yang Ding; Yun-Min Chen (Tunnelling and Underground Space Technology, 2024)

Enhancing microbial salt tolerance through low-voltage stimulation for improved p-chloronitrobenzene (p-CNB) removal in high-salinity wastewater - Long Chen; Li-Ting Zhou; Yang-Cheng Ding; Di Wu; Hua-Jun Feng (Science of The Total Environment, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Shear behavior of cylindrical pin-sleeve connectors of neighboring segments of immersed tunnels - Jiao-Long Zhang; Ding-Li Jin; Yong Yuan; Hong Chen; Zhi-Yuan Hu; Jun-Nan Qiu (Tunnelling and Underground Space Technology, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Behaviour of bamboo scrimber I-beam-box-column connections under static loads - Shao-Bo Kang; Jie-Xin Ding; Jun Xiong; Shu-Rong Zhou; Bin Long (Engineering Structures, 2023)

Collocalia birds inspired Janus-structured bandage with strong wet tissue adhesion for rapid hemostasis and wound healing - Chao Hui; Yuan Gao; Bing-Yu Yan; Li-Qiang Ding; Tian-Cai Sun; Zhong Liu; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2023)

Mxene composite fibers with advanced thermal management for inhibiting tumor recurrence and accelerating wound healing - Yining Ding; Lei Xu; Shengnan Chen; Youfu Zhu; Yuehua Sun; Liqiang Ding; Bingyu Yan; Seeram Ramakrishna; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2023)

Giant Mesozoic gold ores derived from subducted oceanic slab and overlying sediments - Kun-Feng Qiu; Jun Deng; Crystal Laflamme; Zheng-Yu Long; Ruo-Qi Wan; Frederic Moynier; Hao-Cheng Yu; Jing-Yuan Zhang; Zheng-Jiang Ding; Richard Goldfarb (Geochimica et Cosmochimica Acta, 2023)

Estimation of earth pressure against retaining walls with different limited displacement modes based on elastic theory - Le Zhang; Fa-ning Dang; Xu Wang; Jiu-long Ding; Jun Gao; Yu Zhang (Journal of Mountain Science, 2022)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Relationships between soil respiration and hyperspectral vegetation indexes and crop characteristics under different warming and straw application modes - Sicheng Ding; Xuewen Yao; Jin Wang; Ximing Deng; Miaomiao Zhang; Jilan Long; Shutao Chen; Zhenghua Hu; Dan Wang; Yanling Wang; Jun Wang; Tingting Zhang (Environmental Science and Pollution Research, 2021)

The co-evolution of life and organics on earth: Expansions of energy harnessing - Guo-Xin Sun; Song-Can Chen; Gang Li; Xiao-Ming Li; Long-Jun Ding; Brian J. Reid; Philippe Ciais; Yong-Guan Zhu (Critical Reviews in Environmental Science and Technology, 2021)

Down-regulation of MANNANASE7 gene in Brassica napus L. enhances silique dehiscence-resistance - Yu-Long Li; Yan-Kun Yu; Ke-Ming Zhu; Li-Na Ding; Zheng Wang; Yan-Hua Yang; Jun Cao; Li-Zhang Xu; Yao-Ming Li; Xiao-Li Tan (Plant Cell Reports, 2021)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Adventitious root cultures of Oplopanax elatus inhibit LPS-induced inflammation via suppressing MAPK and NF-κB signaling pathways - Wen Tian; Xuan-Mei Piao; Cheng-Ri Yin; Xiao-Long Jiang; Hao-Ding Sun; Xiao-Li An; Jun Jiang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Animal, 2019)

Advances in plant GDSL lipases: from sequences to functional mechanisms - Li-Na Ding; Ming Li; Wei-Jie Wang; Jun Cao; Zheng Wang; Ke-Ming Zhu; Yan-Hua Yang; Yu-Long Li; Xiao-Li Tan (Acta Physiologiae Plantarum, 2019)

Comparison of the characteristics of macrophages derived from murine spleen, peritoneal cavity, and bone marrow - Yan-long Zhao; Pu-xun Tian; Feng Han; Jin Zheng; Xin-xin Xia; Wu-jun Xue; Xiao-ming Ding; Chen-guang Ding (Journal of Zhejiang University-SCIENCE B, 2017)

DNA copy number profiling in microsatellite-stable and microsatellite-unstable hereditary non-polyposis colorectal cancers by targeted CNV array - Weixiang Chen; Jun Ding; Long Jiang; Zebing Liu; Xiaoyan Zhou; Daren Shi (Functional & Integrative Genomics, 2017)

Geographic distance and amorphous iron affect the abundance and distribution of Geobacteraceae in paddy soils in China - Hai-Yan Yuan; Long-Jun Ding; Ning Wang; Song-Can Chen; Ye Deng; Xiao-Ming Li; Yong-Guan Zhu (Journal of Soils and Sediments, 2016)

Arsenic modulates the composition of anode-respiring bacterial community during dry-wet cycles in paddy soils - Ya-Jie Wang; Zheng Chen; Pan-Pan Liu; Guo-Xin Sun; Long-Jun Ding; Yong-Guan Zhu (Journal of Soils and Sediments, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Long‐term balanced fertilization increases the soil microbial functional diversity in a phosphorus‐limited paddy soil - Jian‐Qiang Su; Long‐Jun Ding; Kai Xue; Huai‐Ying Yao; John Quensen; Shi‐Jie Bai; Wen‐Xue Wei; Jin‐Shui Wu; Jizhong Zhou; James M. Tiedje; Yong‐Guan Zhu (Molecular Ecology, 2015)
The influence of long‐term chemical fertilization on soil microbial communities has been one of the frontier topics of agricultural and environmental sciences and is critical for linking soil microbial flora with soil functions. In this study, 16S rRNA gene pyrosequencing and a functional gene array, geochip 4.0, were used to investigate the shifts in microbial composition and functional gene structure in paddy soils with different fertilization treatments over a 22‐year period. These included a control without fertilizers; chemical nitrogen fertilizer (N); N and phosphate (NP); N and potassium (NK); and N, P and K (NPK). Based on 16S rRNA gene data, both species evenness and key genera were affected by P fertilization. Functional gene array‐based analysis revealed that long‐term fertilization significantly changed the overall microbial functional structures. Chemical fertilization significantly increased the diversity and abundance of most genes involved in C, N, P and S cycling, especially for the treatments NK and NPK. Significant correlations were found among functional gene structure and abundance, related soil enzymatic activities and rice yield, suggesting that a fertilizer‐induced shift in the microbial community may accelerate the nutrient turnover in soil, which in turn influenced rice growth. The effect of N fertilization on soil microbial functional genes was mitigated by the addition of P fertilizer in this P‐limited paddy soil, suggesting that balanced chemical fertilization is beneficial to the soil microbial community and its functions.

Induction of autophagy in human neuroblastoma SH-SY5Y cells by tri-ortho-cresyl phosphate - Ding-Xin Long; Dan Hu; Pan Wang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

The role of cell cycle-dependent neuropathy target esterase in cell proliferation - Ping-An Chang; Yu-ying Chen; Wen-zhen Qin; Ding-Xin Long; Yi-Jun Wu (Molecular Biology Reports, 2011)

Protein domains, catalytic activity, and subcellular distribution of mouse NTE-related esterase - Ping-an Chang; Zhan-xiang Wang; Ding-xin Long; Wen-zhen Qin; Yi-jun Wu (Molecular and Cellular Biochemistry, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Metal Pollution in Huayuan River in Hunan Province in China by Manganese Sulphate Waste Residue - Nan Hu; Ji-Fang Zheng; De-Xin Ding; Jun Liu; Lu-Qing Yang; Jie Yin; Guang-Yue Li; Yong-Dong Wang; Yu-Long Liu (Bulletin of Environmental Contamination and Toxicology, 2009)

Molecular cloning and expression of the C-terminal domain of mouse NTE-related esterase - Ping-An Chang; Ding-Xin Long; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)